A pattern of skin diseases in a tertiary hospital in Djibouti: a retrospective study between January 2018 and December 2021 - Moussa, Iftin Osman (International Journal of Research in Dermatology, 2022)
Background: Skin diseases differ in various countries and social, hygiene, and weather conditions are contributing factors as well. We aim to describe, for the first time, the frequency of the skin disease spectrum in the Djiboutian population. The aim was to find out the spectrum of cutaneous diseases in relation to age, sex, origin, and season variation. Methods: This was a single-center, retrospective study on new patients attending a dermatology tertiary hospital in Djibouti between January 2018 and December 2021. Disease frequencies and prevalence by sex, seasons, and age group were recorded. Results: There were 9114 new patients. The male/female ratio was 0.55, with 5897 females (64.70%) and 3217 males (32.45%). The mean age was 23.1 years, ranging from 3 weeks old to 97 years old. The most common diagnoses were scabies 12.83% (n=1169), contact dermatitis 10.97% (n=1000) and dermatophytosis 7.93% (n=723). Skin infections were the commonest diagnostic group and amounted to 43.65% (n=3978). Conclusions: We found a higher prevalence of infectious dermatoses, with scabies dominating. In order to design both preventive and curative healthcare services, appropriate public health policy necessitates an understanding of skin disease epidemiology.